Trade protection and firm innovation in China - Huang, Tao (International journal of emerging markets, 2024)
PurposeThe author investigates the effect of trade protection on domestic firm innovation in China and explores the channel through which trade protection affects corporate innovation.Design/methodology/approachUsing a sample of Chinese A-share manufacturing companies from 2003 to 2019, the author starts with a univariate analysis by examining the innovation output after trade protection for all samples. The author uses the natural logarithm of one plus the number of trade protection cases received by the industry to which the firm belongs in a particular year to proxy for trade protection.FindingsThe author finds that trade protection significantly encourages firms’ patent application, particularly substantive patents, which is stronger in non-state-owned enterprises. Moreover, the mitigation of financial constraint is plausible channel that allows trade protection to promote innovation.Practical implicationsFor practitioners, they should seize the dividends of national policies. In the process of implementing trade protection, they should concentrate on improving their innovation level and enhancing their core competitiveness. When they are not subject to trade protection, they can also make profits and develop in the long run.Social implicationsFor policy makers, in the early stage of industry development, trade protection can be used to ease the companies’ financing constraints and improve the companies’ profits, which will help them concentrate their efforts, promote innovation and further develop. However, in the mid-term development of the industry, policy makers should reduce trade protection. Through the entry of foreign capital, companies face increased competition, which can enhance the companies’ motivation for long-term development.Originality/valueOverall, this paper sheds light on the real effects of trade protection and the determinants of innovation. First, the paper sheds light on the impact of international trade on firms’ innovation. Second, this study also contributes to the emerging literature on the effect of trade policy uncertainty on financial constraint. Third, the paper adds to the stream of literature on the drivers of innovation.